A dry powder dry-pressed fusion welding type lithium-doped manganese-aluminum energy storage battery and a preparation method thereof

CN122930810APending Publication Date: 2026-10-16SICHUAN ALUMINUM NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611139185.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

其中,铅酸电池的寿命较短,深度循环仅能达到500至800次;且其能量密度极低,低温衰减严重,自放电大;并且其含重金属铅与硫酸腐蚀体系,环保压力巨大、回收成本较高、全生命周期经济性差

Benefits of technology

[0017] Compared to the prior art, the dry powder dry pressing fusion welding lithium-free manganese aluminum energy storage battery and its preparation method provided in this application can provide an energy storage battery with some or all of the advantages of high safety, high environmental adaptability, long cycle life, low cost, green environmental protection and mass production. It can also make it take into account multiple core advantages such as no dependence on scarce mineral resources, compatibility with dry powder preparation and thick sheet forming process, and excellent high and low temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930810A_ABST
    Figure CN122930810A_ABST
Patent Text Reader

Abstract

The application relates to the field of green energy storage batteries, in particular to a preparation method of a dry powder dry-pressing fusion welding type lithium-doped manganese-aluminum energy storage battery, which comprises the following steps: uniformly mixing aluminum powder, manganese powder, copper powder, tin powder and rosin powder according to a predetermined proportion, filling the mixed material into through filling holes of an electrode plate, and synchronously dry-pressing the mixed material and the electrode plate to pre-form an integrated green body, heating and solidifying the mixed material in the integrated green body to form a negative electrode sheet which is integrally fusion-welded and consolidated; uniformly mixing bismuth powder and manganese dioxide by dry grinding in advance according to a predetermined proportion, then adding predetermined proportions of graphite, graphene, silver powder and rosin powder into the mixed material and uniformly mixing the mixed material, and dry-pressing the mixed material to form a positive electrode sheet with micropores reserved in the interior; alternately arranging the positive electrode sheet and the negative electrode sheet in a shell through a diaphragm, injecting a weak alkaline composite electrolyte into the shell, and performing primary electrochemical formation treatment to complete the preparation of the energy storage battery. The application has the advantages of high safety, long cycle life, green environmental protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of green energy storage batteries, and in particular to a dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery and its preparation method. Background Technology

[0002] Currently, the mainstream energy storage batteries on the market are lead-acid batteries and lithium batteries. Lead-acid batteries have a short lifespan, with a deep cycle life of only 500 to 800 cycles; they also have extremely low energy density, severe low-temperature degradation, and high self-discharge; furthermore, their system, containing heavy metal lead and sulfuric acid corrosion, faces significant environmental pressure, high recycling costs, and poor overall life-cycle economics. Lithium iron phosphate / lithium batteries rely on lithium ore resources, whose prices fluctuate wildly; their production requires wet pulping, organic solvents, high-temperature drying, and vacuum liquid injection, resulting in huge equipment investment; and they pose safety hazards such as thermal runaway, fire, and explosion, requiring complex BMS (Battery Management System) equalization and thermal management systems, leading to high overall costs and insufficient low-temperature performance in northern regions.

[0003] Because both lead-acid and lithium batteries have unavoidable shortcomings in performance, cost, safety, and environment, the industry has always lacked energy storage batteries that have comprehensive advantages. Therefore, various new energy storage batteries have become the core direction of industry research and development. However, among the new energy storage batteries that have been industrialized, traditional aluminum-manganese batteries still have significant technical bottlenecks and are difficult to overcome application limitations.

[0004] Traditional aluminum-manganese batteries use ordinary aluminum as the negative electrode, which is prone to hydrogen evolution corrosion, plate pulverization and detachment during operation, directly leading to a significant reduction in cycle life and insufficient durability. The positive electrode uses manganese dioxide, which has a low voltage plateau and severe manganese dissolution during operation, greatly limiting the improvement of energy density and resulting in weak energy storage efficiency. At the same time, the overall structure of the battery electrode is loose, the internal conductive network has poor stability, and the process adaptability is extremely poor, making it impossible to achieve thick sheet molding and large-scale mass production, which seriously restricts its industrialization and application.

[0005] Therefore, developing an energy storage battery that combines some or all of the advantages of high safety, high environmental adaptability, long cycle life, low cost, green environmental protection and mass production, and can also take into account multiple core advantages such as no dependence on scarce mineral resources, compatibility with dry powder preparation and thick sheet molding processes, and excellent high and low temperature performance, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0006] This application provides a dry powder dry pressing fusion welding lithium-free doped manganese aluminum energy storage battery and its preparation method, so as to provide an energy storage battery with some or all of the advantages of high safety, high environmental adaptability, long cycle life, low cost, green environmental protection and mass production. It can also make it have multiple core advantages such as no dependence on scarce mineral resources, adaptability to dry powder preparation and thick sheet forming process, and excellent high and low temperature performance.

[0007] To solve the above-mentioned technical problems, this application provides the following technical solution: A method for preparing a dry-powder, dry-pressed, fusion-welded lithium-free manganese-aluminum energy storage battery includes the following steps: aluminum powder, manganese powder, copper powder, tin powder, and rosin powder are mixed according to a predetermined ratio; the mixture is filled into the through-filler holes of an electrode plate, and the mixture and electrode plate are simultaneously dry-pressed and pre-formed into an integrated green embryo; the mixture in the integrated green embryo is heated and solidified to form an integrally fused and solidified negative electrode sheet; bismuth powder and manganese dioxide are pre-dry-ground and mixed evenly according to a predetermined ratio, and then graphite, graphene, silver powder, and rosin powder are added and mixed evenly; the mixture is dry-pressed and formed into a positive electrode sheet with internal micropores; the positive and negative electrode sheets are alternately arranged in a separator within a casing; a weakly alkaline composite electrolyte is injected into the casing, and a primary electrochemical formation treatment is performed to complete the energy storage battery preparation.

[0008] The preparation method of the dry powder dry-pressed fusion-welded lithium-free manganese-aluminum energy storage battery described above, wherein, preferably, the sub-steps for preparing the negative electrode plate are as follows: aluminum powder, manganese powder, copper powder, and tin powder are mixed evenly according to a predetermined ratio; a predetermined amount of rosin powder is added to the mixture and mixed at a low speed, wherein the ratio of aluminum powder, manganese powder, copper powder, tin powder, and rosin powder is 84%:6%:3%:3%:4%; a layer of the mixture is evenly spread on the pressure-bearing bottom mold; the electrode plate is placed on this layer of mixture; a layer of mixture is evenly spread on the electrode plate, ensuring that the mixture fully fills the through-filling holes of the electrode plate; after completing the spreading, the pressure-bearing top mold is... Under high pressure and ambient temperature conditions between 14MPa and 30MPa, the laminated mixture and electrode plate are simultaneously dry-pressed and pre-formed to obtain an integrated green blank. The thickness of the mixture after dry pressing and pre-forming in the through-filler holes is controlled between 2.1mm and 2.2mm. Under constant temperature conditions between 230℃ and 235℃, the mixture in the integrated green blank is cured for 3 to 4 minutes. During the curing process, rosin powder deoxidizes the metal powder, and tin powder undergoes critical micro-melting to form full-area metal solder joints. The integrated green blank is then slowly cooled to reduce the thickness of the mixture in the through-filler holes to 2mm, resulting in an integrally fused and solidified negative electrode sheet.

[0009] In the preparation method of the dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery as described above, preferably, the safe adjustable range of the proportions of aluminum powder, manganese powder, copper powder, tin powder and rosin powder in the mixture of negative electrode sheet is: aluminum powder 82%~85%, manganese powder 5%~7%, copper powder 2.5%~3.5%, tin powder 2.5%~3.5%, and rosin powder 3.5%~4.5%.

[0010] The preparation method of the dry powder dry pressing fusion welding type lithium-free manganese aluminum energy storage battery as described above, wherein, preferably, the sub-steps for preparing the positive electrode plate are as follows: Bismuth powder and manganese dioxide are pre-dry ground and mixed uniformly according to a predetermined ratio to obtain a dry powder-grade lattice modified substrate powder, wherein the bismuth powder accounts for 1%–8% and the manganese dioxide accounts for 92%–99%; a predetermined ratio of graphite, graphene, and silver powder is added to the dry powder-grade lattice modified substrate powder and mixed uniformly; a predetermined amount of rosin powder is added to the mixture and mixed at a low speed, wherein the dry powder-grade lattice modified substrate powder, graphite, and silver powder are mixed uniformly. The ratio of graphene, silver powder, and rosin powder is 86%:6%:4%:3%:1%. A layer of mixture is evenly spread on the pressure-bearing bottom mold, and the electrode plate is placed on this layer of mixture. A layer of mixture is evenly spread on the electrode plate, and the mixture is made to fully fill the through-filling holes of the electrode plate. After the material is spread, the pressure-bearing top mold is subjected to room temperature between 14MPa and 30MPa, and the stacked mixture and the electrode plate are simultaneously dry-pressed to form a positive electrode sheet with complete through-filling micropores in the mixture. The thickness of the mixture after dry pressing in the through-filling holes is controlled to be 2mm.

[0011] In the preparation method of the dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery as described above, preferably, the safe adjustable range of the proportions of dry powder-grade lattice modified substrate powder, graphite, graphene, silver powder, and rosin powder in the mixture of positive electrode sheet is: 85-87% dry powder-grade lattice modified substrate powder, 5.5-6.5% graphite, 3.5-4.5% graphene, 2.8-3.2% silver powder, and 0.8-1.2% rosin powder.

[0012] In the preparation method of the dry powder dry pressure welding type lithium-free manganese aluminum energy storage battery described above, preferably, after the weak alkaline composite electrolyte is fully impregnated with the negative electrode and the positive electrode by being left to stand at room temperature, the assembled energy storage battery is subjected to the first electrochemical formation treatment.

[0013] The preparation method of the dry powder dry-pressed fusion-welded lithium-free manganese-aluminum energy storage battery described above, wherein preferably, the preparation steps of the weakly alkaline composite electrolyte are as follows: using deionized water as the base solvent, aluminum chloride is added in batches to the base solvent under stirring at room temperature. After the dissolution and exothermic reaction stabilize, manganese chloride is added and stirred until completely dissolved; glycerol and sodium silicate are added sequentially and stirred until well mixed; dilute ammonia is added dropwise under continuous low-speed stirring to adjust the pH value to the weakly alkaline range of 9.0 to 9.8; after standing to remove impurities and filtering, the weakly alkaline composite electrolyte is obtained.

[0014] In the preparation method of the dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery as described above, preferably, the total molar concentration of aluminum chloride and manganese chloride is controlled between 3.0 mol / L and 3.8 mol / L, and the molar ratio of aluminum chloride to manganese chloride is in the range of (2 to 4):1.

[0015] In the preparation method of the dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery as described above, preferably, the amount of glycerol added is 0.5 g / L to 3.0 g / L, and the amount of sodium silicate added is 0.3 g / L to 2.0 g / L.

[0016] A dry powder dry pressure welding type lithium-free manganese aluminum energy storage battery includes: a shell and multiple cells, the multiple cells are connected in series and the multiple cells connected in series are located inside the shell; each cell includes: multiple positive electrode plates, multiple negative electrode plates and a weak alkaline composite electrolyte, the positive electrode plates and negative electrode plates are alternately arranged with separation by a membrane inside the cell shell, and the weak alkaline composite electrolyte is injected into the cell shell.

[0017] Compared to the prior art, the dry powder dry pressing fusion welding lithium-free manganese aluminum energy storage battery and its preparation method provided in this application can provide an energy storage battery with some or all of the advantages of high safety, high environmental adaptability, long cycle life, low cost, green environmental protection and mass production. It can also make it take into account multiple core advantages such as no dependence on scarce mineral resources, compatibility with dry powder preparation and thick sheet forming process, and excellent high and low temperature performance. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings.

[0019] Figure 1 This is a schematic diagram of a dry powder dry-pressed fusion-welded lithium-free manganese-aluminum energy storage battery. Figure 2 This is a schematic diagram of a dry-powder, dry-pressed, welded lithium-free manganese-aluminum doped energy storage battery cell. Figure 3 This is a schematic diagram of the positive and negative electrode plates of a dry powder dry pressing fusion welding type lithium-free manganese-aluminum doped energy storage battery; Figure 4 yes Figure 3 Sectional view along line AA in the middle; Figure 5 This is a flowchart of the preparation method of a dry powder dry pressing fusion welding type lithium-free doped manganese aluminum energy storage battery. Detailed Implementation

[0020] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0021] Example 1 like Figures 1 to 4 As shown, this application provides a dry powder dry pressure welding type lithium-free manganese aluminum energy storage battery, including: a casing 110 and multiple cells 120; wherein, each cell 120 includes: multiple positive electrode plates, multiple negative electrode plates and a weakly alkaline composite electrolyte, the positive electrode plates and negative electrode plates are alternately arranged with separation in the cell casing, and the weakly alkaline composite electrolyte is injected into the cell casing; the multiple cells 120 are connected in series, and the multiple cells 120 connected in series are located in the casing 110.

[0022] The electrode plate 200 has multiple through-filler holes 210; the mixture 220 filled in the through-filler holes 210 is a predetermined ratio of aluminum powder, manganese powder, copper powder, tin powder and rosin powder, and is heated and cured to form an integrally fused and solidified negative electrode sheet; the mixture 220 filled in the through-filler holes 210 is a predetermined ratio of dry powder-grade lattice modified substrate powder, graphite, graphene, silver powder and rosin powder, and is dry-pressed into a positive electrode sheet with micropores inside, wherein the dry powder-grade lattice modified substrate powder is a predetermined ratio of bismuth powder and manganese dioxide that is dry-ground and mixed evenly.

[0023] Example 2 like Figure 5 As shown, this application provides a method for preparing a dry powder dry pressing fusion-welded lithium-free manganese-aluminum energy storage battery, comprising the following steps: Step S510: Mix aluminum powder, manganese powder, copper powder, tin powder and rosin powder according to the predetermined ratio, fill the mixture into the through filling hole of the electrode plate, and simultaneously dry press the mixture and the electrode plate to preform into an integrated green blank. Heat and solidify the mixture in the integrated green blank to form an integrally fused and solidified negative electrode sheet.

[0024] The sub-steps for preparing the negative electrode plate are as follows: (1) Mix aluminum powder, manganese powder, copper powder and tin powder according to the predetermined ratio; (2) Add a predetermined amount of rosin powder to the mixture and mix at a low speed (e.g., 30r / min to 60r / min) to prevent the rosin powder from caking when heated during the mixing process. The ratio of aluminum powder, manganese powder, copper powder, tin powder and rosin powder is 84%:6%:3%:3%:4%; (3) First, spread a layer of mixture evenly on the pressure-bearing bottom mold, then place the electrode plate on the layer of mixture, and then spread a layer of mixture evenly on the electrode plate, and make the mixture fully fill the through-filling hole of the electrode plate. After the material is spread, make the pressure-bearing top mold under high pressure and normal temperature (e.g., 20℃ to 25℃) between 14MPa and 30MPa to test the stacked mixture and the electrode plate. The electrode plate is synchronously dry-pressed and preformed to obtain an integrated green blank, and the thickness of the mixed material after dry-pressing and preforming in the through-filler hole is controlled between 2.1mm and 2.2mm; (4) The integrated green blank is sent into a hot air oven and the mixed material in the integrated green blank is cured for 3 to 4 minutes under a constant temperature of 230℃ to 235℃. During the curing process, rosin powder deoxidizes the metal powder and tin powder is critically micro-melted to form a full-area metal solder joint; (5) After curing for 3 to 4 minutes, the integrated green blank is slowly cooled in the hot air oven so that the rosin is completely volatilized, the micropores inside the mixed material shrink evenly, and the full-area metal solder joint is fully shaped, so that the thickness of the mixed material in the through-filler hole shrinks to 2mm, and the overall fused and solidified negative electrode sheet is obtained.

[0025] The functions of each component are as follows: Aluminum powder: the core active energy storage component of the negative electrode sheet, possessing extremely high theoretical specific capacity, which can provide sufficient energy storage capacity for the negative electrode sheet.

[0026] Manganese powder: Trace amounts of manganese atoms can dissolve in the grain boundaries of aluminum grains, effectively hindering the migration, agglomeration and coarsening of aluminum grains, refining coarse aluminum grains into uniform and fine micro-grains, greatly improving the structural compactness and stability of the negative electrode sheet, increasing the active sites of the negative electrode sheet, and is a core stabilizer for long-cycle operation.

[0027] Furthermore, manganese possesses moderate redox activity, which can replace or destroy the dense alumina passivation film formed on the aluminum surface in the electrolyte, while simultaneously reconstructing a loose, highly conductive, and highly permeable composite passivation film. This not only prevents excessive oxidation of the aluminum surface but also ensures smooth electrolyte penetration and free ion migration, completely solving the problems of reaction lag and low activity caused by the alumina passivation film. It can also effectively reduce the corrosion potential of the aluminum substrate, inhibit the self-corrosion kinetic rate of aluminum, significantly weaken the reactivity between the electrolyte and the aluminum substrate, inhibit the occurrence of hydrogen evolution reaction from the root, and reduce the ineffective loss of active materials.

[0028] The composite passivation film is formed by the negative electrode sheet in a weakly alkaline composite electrolyte (aluminum chloride-manganese chloride). From the inside out, it consists of a manganese-doped aluminum hydroxide barrier layer (Al2O3, Al(OH)3, and trace amounts of Mn). 2+ Doped aluminum hydroxyl oxide (Mn-Al-LDH) and multivalent manganese hydroxyl oxide layers (MnO, MnO2, Mn(OH)). x The three-layer porous hybrid interface film consists of a porous hydrated manganese aluminum silicate composite gel layer. The inner layer is a manganese-doped aluminum hydroxide barrier layer that prevents the aluminum substrate from reacting violently with the weakly alkaline composite electrolyte, reducing the aluminum corrosion potential and inhibiting continuous hydrogen evolution. The middle layer is a multivalent manganese hydroxyl oxide layer that forms a manganese-silicon-aluminum composite conductive framework. The outer layer is a porous ion-conducting layer.

[0029] Copper powder can fill the microscopic gaps between aluminum powder, manganese powder, and tin powder, effectively reducing the contact breaks between various metal powders, significantly reducing the overall internal resistance of the negative electrode sheet, and stabilizing the electrochemical performance of the energy storage battery.

[0030] Tin powder: Its melting point is 231.9℃. The temperature of 230℃ to 235℃ is exactly the critical melting point of tin powder. The surface of tin powder is in a critical micro-melting state. In this state, the whole does not flow, collapse, or clump. It can bond and weld adjacent aluminum powder, copper powder, and manganese powder together, forming countless micro-metal solder points inside the entire negative electrode sheet. These metal solder points are distributed throughout the entire negative electrode sheet. After cooling and forming, all metal powders are firmly locked into a dense solid whole by the metal solder points, thus solving the problems of loose structure, unstable conductivity, inability to form thick sheets, and cyclic powdering and shedding of the negative electrode sheet in traditional aluminum-manganese batteries.

[0031] If the curing temperature is too low, the tin powder cannot adhere and fuse to form a full-area metal solder joint, resulting in a higher internal resistance of the negative electrode sheet. If the curing temperature is too high, the molten tin will flow excessively, easily blocking the micropores inside the negative electrode sheet, significantly reducing the effective reaction interface, increasing ion transport resistance, significantly increasing the degree of electrode polarization, and causing a decline in the electrochemical performance of the energy storage battery.

[0032] Rosin powder: The temperature range of 230℃ to 235℃ is the high activity range of rosin. At this temperature, the rosin powder will be activated to remove the oxide layer (aluminum oxide, copper oxide, tin oxide) naturally present on the surface of the metal powder (aluminum powder, copper powder, tin powder), exposing the pure metal interface of the metal powder. The molten rosin will also coat all the metal powder, isolating the metal powder from the air and preventing the metal powder from being oxidized again during the high temperature heating process. This ensures that the metal powder can be completely welded together, thereby ensuring the conductivity of the negative electrode.

[0033] In addition, the thickness of the dry-pressed preformed mixture is controlled between 2.1mm and 2.2mm, and the proportion of rosin powder is 4%. It is cured at a constant temperature between 230℃ and 235℃. The rosin evaporates and releases volume, and the tin powder melts and fills the micro-gap between the metal powders. This allows the mixture with a thickness of 2.1mm to 2.2mm to be accurately molded into a thickness of 2.0mm.

[0034] In addition, the ratio of aluminum powder, manganese powder, copper powder, tin powder, and rosin powder in the mixture is 84%:6%:3%:3%:4%, with aluminum powder accounting for 84%. If the proportion of aluminum powder is too much greater than 84%, the manganese, copper, and tin will be diluted, and the aluminum particles will expand and pulverize out of control during charging and discharging, resulting in a sharp increase in capacity decay. If the proportion of aluminum powder is too much less than 84%, the active aluminum content will decrease, and the actual capacity of the energy storage battery will shrink.

[0035] The manganese powder content is 6%. If the manganese powder content is too high (more than 6%), the inert manganese will not have storage capacity and will crowd out the aluminum content, resulting in a decrease in the capacity of the energy storage battery. In addition, the high hardness of manganese and poor dry pressing flow will lead to uneven local density of the negative electrode sheet and an increase in internal resistance. If the manganese powder content is too high (less than 6%), the aluminum-manganese alloying will be insufficient, the aluminum particles will expand and scatter significantly during charging and discharging, the cycle life will drop sharply, and the composite passivation film will be easily lost. The aluminum will be continuously corroded and swell by the electrolyte, which will lead to the bulging and failure of the energy storage battery.

[0036] The copper powder content is 3%. If the copper powder content is too high, the capacity of the energy storage battery will decrease because copper has no storage capacity and will crowd out the aluminum content. In addition, the high density of copper will lead to an increase in the weight of the negative electrode, a decrease in energy density, and an increase in cost. If the copper powder content is too high, the number of conductive breaks between metal powders will increase, the internal resistance of the negative electrode will increase, and the high-power discharge voltage drop will be severe.

[0037] The tin powder content is 3%. If the tin powder content is too high, the volume expansion of tin during charging and discharging will be too large. Excessive tin will pulverize itself and backfire on the negative electrode. In addition, due to the high unit price of tin, the raw material cost will increase significantly. If the tin powder content is too high, there is a lack of liquid buffer phase. The expansion of aluminum will not be buffered, and the negative electrode will break down and shed active material in cycles.

[0038] The rosin content should be 4%. If the rosin content is too high, excessive inert carbon will remain after high-temperature carbonization, reducing compaction density and capacity. Furthermore, the residual organic matter will continue to decompose and produce gas, causing the energy storage battery to swell. In addition, too much inactive component will reduce the energy density of the negative electrode. If the rosin content is too high, the bonding force will be insufficient, making it easy to break under dry pressing. Moreover, there will be too few micropores inside the negative electrode, preventing the electrolyte from penetrating into the interior, resulting in poor ion conduction kinetics and poor rate performance.

[0039] Based on the above, the content of a single powder (aluminum powder, manganese powder, copper powder, tin powder, rosin powder) in the mixture can be adjusted within ±2% of its original content, and the adjustment amount should be evenly distributed among the contents of the other powders in the same formula. Specifically, the safe adjustable range for the proportions of each powder in the negative electrode sheet is: aluminum powder 82%–85%, manganese powder 5%–7%, copper powder 2.5%–3.5%, tin powder 2.5%–3.5%, and rosin powder 3.5%–4.5%.

[0040] Step S520: Pre-dry grind and mix bismuth powder and manganese dioxide evenly according to the predetermined ratio, then add graphite, graphene, silver powder and rosin powder in the predetermined ratio and mix evenly, then dry press the mixture into a positive electrode sheet with micropores inside.

[0041] The preparation steps of the positive electrode plate are as follows: (1) Pre-dry grind and mix bismuth powder and manganese dioxide according to a predetermined ratio to obtain dry powder-grade lattice modified substrate powder, wherein the proportion of bismuth powder is 1% to 8% and the proportion of manganese dioxide is 92% to 99%; (2) Add graphite, graphene, and silver powder in a predetermined ratio to the dry powder-grade lattice modified substrate powder and mix well; (3) Add a predetermined amount of rosin powder to the mixture and mix at low speed to prevent the rosin powder from agglomerating when heated during the mixing process, wherein the ratio of dry powder-grade lattice modified substrate powder, graphite, graphene, silver powder, and rosin powder is 86%:6%:4%:3%:1%; (4) First, add the rosin powder to the substrate powder. A layer of mixture is evenly spread on the bottom mold, and then the electrode plate is placed on the mixture. Then, another layer of mixture is evenly spread on the electrode plate, and the mixture is fully filled into the through-filler holes of the electrode plate. After the mixture is spread, the pressure mold is subjected to high pressure and normal temperature (e.g., 20℃~25℃) between 14MPa and 30MPa to simultaneously dry press the stacked mixture and the electrode plate into a positive electrode sheet. The thickness of the mixture after dry pressing in the through-filler holes is controlled to 2mm. No high-temperature welding is required during the dry pressing process of the positive electrode sheet, so that the mixture of the positive electrode sheet retains complete through-pores.

[0042] The functions of each component are as follows: Bismuth powder and manganese dioxide are mixed and rubbed in dry powder, and then micro-extruded to allow the bismuth powder particles to adhere to and penetrate the surface of manganese dioxide grains. This alters the original lattice distortion, pore structure, conductivity, and redox activity of manganese dioxide, creating a dry powder-grade lattice-modified substrate powder. Such a dry powder-grade lattice-modified substrate powder can improve the conductivity, rate performance, and voltage boosting characteristics of the positive electrode.

[0043] During the initial electrochemical formation process, bismuth ions automatically embed into the manganese dioxide lattice, thereby raising the overall discharge potential, increasing the discharge voltage platform by 0.08V to 0.16V, and increasing the energy density by 15% to 20%. At the same time, it suppresses the dissolution of manganese ions, significantly improving the cycle stability of the positive electrode, and achieving a high-energy-density upgrade with no process increment and low-cost voltage boost.

[0044] Manganese dioxide: The main active redox raw material for positive electrode sheets, it has stable potential, huge reserves, and low cost.

[0045] Graphite: It builds a continuous conductive path inside the powder, reduces the overall internal resistance of the positive electrode, buffers dry pressure stress, enhances the mechanical structural toughness of the positive electrode, prevents the positive electrode from cracking under pressure, and improves the overall conductivity and molding structure stability of the positive electrode.

[0046] Graphene: It fills the internal micropores, shortens the ion migration path, reduces the electrochemical polarization voltage drop, alleviates voltage decay under high current, and significantly improves the fast charging and discharging capability and high-rate discharge performance of the positive electrode.

[0047] Silver powder significantly reduces the interfacial contact resistance between powder particles, resulting in outstanding voltage stabilization, a smoother discharge voltage curve, and optimized high-rate discharge characteristics.

[0048] Rosin powder: a dry pressing molding aid that prevents melting and welding during the molding process, ensuring all micropores are connected and guaranteeing smooth electrolyte penetration and ion transport channels.

[0049] Because the positive electrode retains micropores, it can adsorb and retain electrolyte, forming an ion transport pathway that runs through the inside of the positive electrode, thus improving the utilization rate of the positive electrode. Furthermore, during the repeated insertion and extraction of cations in the electrolyte, manganese dioxide undergoes microscopic volume expansion and contraction. The micropores of the positive electrode can provide a deformation buffer space, preventing the positive electrode from bulging, cracking, and shedding powder after multiple cycles, thereby extending the lifespan of the positive electrode. In addition, since aluminum-manganese batteries are prone to generating trace amounts of side reaction gases during charging and discharging, the micropores of the positive electrode can guide these trace gases, preventing localized gas trapping, bulging, and electrode delamination within the positive electrode.

[0050] In addition, the negative and positive electrode sheets are uniformly symmetrical with a thickness of 2mm. This ensures that the expansion and contraction stress of the negative and positive electrode sheets during charging and discharging are perfectly matched. As a result, the battery cell composed of the negative and positive electrode sheets does not deform, warp, or bulge, solving the problem of cycle degradation and cracking in thick-sheet energy storage batteries. Furthermore, the negative and positive electrode sheets are manufactured using a solvent-free dry process, making the production of energy storage batteries more environmentally friendly, lower in cost, and with a higher yield.

[0051] Furthermore, the proportions of dry-grade lattice-modified substrate powder, graphite, graphene, silver powder, and rosin powder in the mixture are 86%:6%:4%:3%:1%. Among them, the proportion of dry-grade lattice-modified substrate powder is 86%. If the proportion of some dry-grade lattice-modified substrate powder is too high (greater than 86%), the conductive phase (graphite / graphene / silver) will not be sufficiently compressed. Moreover, due to the poor semiconductor conductivity of manganese dioxide, the internal resistance of the positive electrode sheet will increase dramatically, resulting in extremely poor high-current discharge performance. In addition, due to the compressed proportion of rosin powder, the mixture will not bond sufficiently during dry pressing, making it prone to cracking. Furthermore, the lack of carbonaceous buffering will accelerate the collapse of the manganese dioxide lattice during charge and discharge, leading to faster cycle decay. If the proportion of some dry-grade lattice-modified substrate powder is too high (greater than 86%), the active main material will be squeezed out by inactive conductive fillers, resulting in a significant reduction in the actual capacity of the positive electrode sheet and a decrease in the energy density of the energy storage battery. Excessive use of auxiliary materials such as graphite and silver will increase the production cost of the positive electrode.

[0052] The graphite content is 6%, and the graphene content is 4%. If the graphite content is too high (greater than 6%) and the graphene content is too high (greater than 4%), it will crowd out the dry powder-grade lattice-modified substrate powder, leading to a decline in the capacity of the energy storage battery. In addition, the carbon material is loose, and the density of dry pressing is reduced, resulting in a decrease in the energy density of the energy storage battery. If the graphite content is too low (greater than 6%) and the graphene content is too low (greater than 4%), the carbon conductive network is incomplete, the powder in the dry powder-grade lattice-modified substrate powder is isolated, and a large number of active materials cannot participate in the electrochemical reaction, resulting in a drop in the effective capacity of the energy storage battery, severe polarization, and incomplete charging.

[0053] The silver powder content is 3%. If the silver powder content is too much greater than 3%, the cost of the energy storage battery caused by precious metals will soar. Moreover, since silver has no storage capacity activity, it will squeeze the capacity of the main material. If the silver powder content is too much less than 3%, the number of conductive breaks in the positive electrode will increase, the internal resistance will rise sharply, the polarization loss will increase, and the actual usable capacity will be reduced.

[0054] The rosin powder content is 1%. If the rosin powder content is too high, the organic matter will decompose at high temperature and leave behind impurities and gases, which will increase the polarization of the positive electrode and cause the energy storage battery to swell. If the rosin powder content is too high, the dry pressing bonding will be insufficient, the positive electrode will shed powder, and the assembly yield will plummet.

[0055] Based on the above, the content of a single powder (dry-grade lattice-modified substrate powder, graphite, graphene, silver powder, rosin powder) in the mixture can be adjusted within ±2% of its original content, and the adjustment amount of this powder is evenly distributed among the contents of the other powders in the same formula. Specifically, the safe and adjustable range for the proportions of each powder in the positive electrode sheet is: dry-grade lattice-modified substrate powder 85–87%, graphite 5.5–6.5%, graphene 3.5–4.5%, silver powder 2.8–3.2%, and rosin powder 0.8–1.2%.

[0056] Step S530: The positive and negative electrode sheets are alternately arranged in the shell with the separator, a weak alkaline composite electrolyte is injected into the shell, and the first electrochemical formation treatment is performed to complete the preparation of the energy storage battery. The positive and negative electrode sheets are alternately arranged in the casing, and an insulating porous membrane is installed between adjacent positive and negative electrode sheets to physically isolate them and prevent direct contact that could cause an internal short circuit. A certain amount of weakly alkaline composite electrolyte is injected into the casing. After standing at room temperature to allow the weakly alkaline composite electrolyte to fully wet the negative and positive electrode sheets, the assembled energy storage battery is subjected to the initial electrochemical formation treatment using a low-current, low-rate mode. This slowly drives the cations in the electrolyte to repeatedly insert and extract between the crystal lattices of the positive and negative electrode sheets, gradually clearing the ion transport channels inside the positive electrode sheet, releasing the internal stress generated during the positive electrode sheet preparation process, activating the crystal structure of the negative and positive electrode sheets, ensuring the capacity and cycle stability of the energy storage battery, and completing the preparation of the energy storage battery.

[0057] A weakly alkaline composite electrolyte uses deionized water as the base solvent. Aluminum chloride is added in batches to the base solvent under stirring at room temperature. After the dissolution and exothermic reaction stabilize, manganese chloride is added and stirred until completely dissolved. The total molar concentration of aluminum chloride and manganese chloride is controlled between 3.0 mol / L and 3.8 mol / L, with a molar ratio of aluminum chloride to manganese chloride ranging from (2 to 4):1, preferably 2.5:1. Glycerol and sodium silicate are then added sequentially and stirred until homogeneous. The amount of glycerol added is 0.5 g / L to 3.0 g / L, preferably 1.0 g / L to 2.0 g / L, and the amount of sodium silicate added is 0.3 g / L to 2.0 g / L, preferably 0.5 g / L to 1.2 g / L. g / L; then, under continuous low-speed stirring, dilute ammonia water is added dropwise to adjust the pH value to a weakly alkaline range of 9.0 to 9.8. The weakly alkaline pH value is suitable for the negative electrode sheet, does not corrode, does not evolve hydrogen, and does not dissolve aluminum. The pH value is preferably controlled in the weakly alkaline range of 9.2 to 9.5. Finally, after standing to remove impurities and filtering, a weakly alkaline composite electrolyte is obtained.

[0058] The functions of each component are as follows: Aluminum chloride and manganese chloride: Match the positive and negative electrode plates to reduce manganese dissolution and stabilize the interface; Glycerin: Reduces viscosity, suitable for deep wetting of positive and negative electrode sheets with a thickness of 2mm; Sodium silicate: helps form a stable composite passivation film, effectively inhibiting the corrosion of aluminum by electrolyte.

[0059] Compared to traditional unmodified manganese-aluminum batteries, the energy storage battery of this application can increase the discharge voltage platform from 1.30V-1.45V to 1.45V-1.60V. The integrated welded negative electrode can achieve 1600-2300 cycles, far exceeding the 800-1200 cycles of traditional aluminum negative electrode sheets. Its energy density reaches 115Wh / kg-155Wh / kg, more than twice that of lead-acid batteries (30Wh / kg-50Wh / kg). Its capacity retention at -20℃ is 85%-93%, significantly surpassing that of lead-acid batteries. The battery retains 55%–65% of its capacity at 0℃. Furthermore, it contains no scarce or heavy metal resources such as lithium, cobalt, nickel, or lead, ensuring a self-sufficient and cost-effective supply chain. It uses a weakly alkaline aqueous electrolyte, possessing inherent safety characteristics of being non-flammable, non-explosive, free from thermal runaway, and non-corrosive / leaking. Additionally, it is produced using a fully dry powder process, eliminating the need for solvents and drying, resulting in zero waste emissions. Equipment investment is only half that of lithium batteries, making the process simple and easy to mass-produce. Moreover, this energy storage battery exhibits low self-discharge, good storage stability, and its mass production cost is close to that of lead-acid batteries, giving it an industry advantage in terms of cost per kilowatt-hour over its entire lifecycle.

[0060] It will be apparent to those skilled in the art that this application is not limited to the details of the exemplary embodiments described above, and that this application can be implemented in other specific forms without departing from the spirit or essential characteristics of this application. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of this application is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this application. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0061] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a dry-powder dry-pressing fusion-welded lithium-free manganese-aluminum energy storage battery, characterized in that, Includes the following steps: Aluminum powder, manganese powder, copper powder, tin powder and rosin powder are mixed evenly according to the predetermined ratio. The mixture is filled into the through-filler hole of the electrode plate and the mixture and the electrode plate are simultaneously dry-pressed to preform into an integrated green blank. The mixture in the integrated green blank is heated and solidified to form an integrally fused and solidified negative electrode sheet. Bismuth powder and manganese dioxide are pre-dry ground and mixed evenly according to a predetermined ratio. Then, graphite, graphene, silver powder and rosin powder are added to the mixture in a predetermined ratio and mixed evenly. The mixture is then dry-pressed into a positive electrode sheet with micropores inside. The positive and negative electrode plates are alternately arranged in a separator inside the casing. A weakly alkaline composite electrolyte is injected into the casing, and the initial electrochemical formation treatment is carried out to complete the preparation of the energy storage battery.

2. The preparation method of the dry powder dry pressing fusion welding type lithium-free manganese-aluminum energy storage battery according to claim 1, characterized in that, The sub-steps for preparing the negative electrode plate are as follows: Mix aluminum powder, manganese powder, copper powder, and tin powder according to the predetermined ratio; Add the predetermined amount of rosin powder to the mixture and mix at low speed. The ratio of aluminum powder, manganese powder, copper powder, tin powder and rosin powder is 84%:6%:3%:3%:4%. A layer of mixture is evenly spread on the pressure-bearing bottom mold. The electrode plate is placed on the layer of mixture, and a layer of mixture is evenly spread on the electrode plate, ensuring that the mixture fully fills the through-filling holes of the electrode plate. After the mixture is spread, the pressure-bearing top mold is subjected to high pressure and normal temperature conditions between 14MPa and 30MPa to simultaneously dry press and preform the stacked mixture and the electrode plate to obtain an integrated green blank. The thickness of the mixture after dry pressing and preforming in the through-filling holes is controlled between 2.1mm and 2.2mm. Under a constant temperature of 230℃ to 235℃, the mixture in the integrated green mold is cured for 3 to 4 minutes. During the curing process, the rosin powder deoxidizes the metal powder, and the tin powder melts at the critical point to form a full-area metal solder joint. The integrated green blank is slowly cooled down, causing the thickness of the mixture in the through-filler holes to shrink to 2mm, resulting in an integrally fused and solidified negative electrode sheet.

3. The preparation method of the dry powder dry pressing fusion welding type lithium-free manganese-aluminum energy storage battery according to claim 2, characterized in that, The safe adjustable range for the proportions of aluminum powder, manganese powder, copper powder, tin powder, and rosin powder in the negative electrode mixture is as follows: Aluminum powder 82%–85%, manganese powder 5%–7%, copper powder 2.5%–3.5%, tin powder 2.5%–3.5%, rosin powder 3.5%–4.5%.

4. The preparation method of the dry powder dry pressing fusion welding type lithium-free manganese-aluminum energy storage battery according to claim 1, characterized in that, The sub-steps for preparing the positive electrode plate are as follows: Bismuth powder and manganese dioxide are pre-dry ground and mixed evenly according to a predetermined ratio to obtain a dry powder-grade lattice-modified substrate powder, wherein the proportion of bismuth powder is 1% to 8% and the proportion of manganese dioxide is 92% to 99%; Add graphite, graphene, and silver powder in a predetermined ratio to dry powder-grade lattice-modified substrate powder and mix well; Add a predetermined amount of rosin powder to the mixture and mix at low speed. The ratio of dry powder-grade lattice modified substrate powder, graphite, graphene, silver powder, and rosin powder is 86%:6%:4%:3%:1%. A layer of mixture is evenly spread on the pressure-bearing bottom mold. The electrode plate is placed on this layer of mixture, and another layer of mixture is evenly spread on the electrode plate, ensuring that the mixture fully fills the through-filling holes of the electrode plate. After the mixture is spread, the pressure-bearing top mold is subjected to high pressure and normal temperature conditions between 14MPa and 30MPa to simultaneously dry-press the stacked mixture and the electrode plate into a positive electrode sheet with complete through-filling micropores in the mixture. The thickness of the mixture after dry-pressing in the through-filling holes is controlled to be 2mm.

5. The preparation method of the dry powder dry pressing fusion welding type lithium-free manganese-aluminum energy storage battery according to claim 4, characterized in that, The safe adjustable range for the proportions of dry-grade lattice-modified substrate powder, graphite, graphene, silver powder, and rosin powder in the positive electrode mixture is as follows: The dry powder-grade lattice-modified substrate powder contains 85-87% graphite, 5.5-6.5% graphene, 3.5-4.5% silver powder, 2.8-3.2% rosin powder, and 0.8-1.2% rosin powder.

6. The method for preparing a dry powder dry pressing fusion-welded lithium-free manganese-aluminum energy storage battery according to claim 1, characterized in that, After allowing the weakly alkaline composite electrolyte to fully wet the negative and positive electrode plates at room temperature, the assembled energy storage battery undergoes its first electrochemical formation treatment.

7. The method for preparing a dry powder dry pressing fusion-welded lithium-free manganese-aluminum energy storage battery according to claim 1, characterized in that, The preparation steps of the weakly alkaline composite electrolyte are as follows: Using deionized water as the base solvent, aluminum chloride was added in batches to the base solvent under stirring at room temperature. After the dissolution and exothermic reaction stabilized, manganese chloride was added and stirred until completely dissolved. Add glycerin and sodium silicate in sequence and stir until well mixed; Add dilute ammonia dropwise while stirring continuously at low speed to adjust the pH value to a slightly alkaline range of 9.0 to 9.8; After standing to remove impurities and filtering, a weakly alkaline composite electrolyte is obtained.

8. The method for preparing a dry powder dry pressing fusion-welded lithium-free manganese-aluminum energy storage battery according to claim 7, characterized in that, The total molar concentration of aluminum chloride and manganese chloride was controlled between 3.0 mol / L and 3.8 mol / L, and the molar ratio of aluminum chloride to manganese chloride was (2-4):

1.

9. The method for preparing a dry powder dry pressing fusion-welded lithium-free manganese-aluminum energy storage battery according to claim 7, characterized in that, The amount of glycerol added is 0.5 g / L to 3.0 g / L, and the amount of sodium silicate added is 0.3 g / L to 2.0 g / L.

10. A dry-powder, dry-pressed, fusion-welded lithium-free manganese-aluminum energy storage battery, characterized in that, include: The casing and multiple battery cells are connected in series, and the multiple battery cells connected in series are located inside the casing; Each cell includes: multiple positive electrode plates, multiple negative electrode plates, and a weakly alkaline composite electrolyte. The positive and negative electrode plates are arranged alternately and separated by a diaphragm inside the cell housing, and the weakly alkaline composite electrolyte is injected into the cell housing.